Coconut rhinoceros beetle, Oryctes rhinoceros (Coleoptera: Scarabaeidae), larval frass as plant fertilizer - Chiao-Jung Han; Zeng-Yei Hseu; Po-Hui Wu; Louis Grillet; Chun-Han Ko; Matan Shelomi (Botanical Studies)
Abstract Background Beetle rearing for food or feed is a growing area of agriculture that produces considerable wastes. This frass is a putative soil amendment anecdotally applied directly as fertilizer. To determine if beetle waste can be used as a soil amendment without pre-treatment, a series of chemical, physical, microbiological, and plant-growth assays were performed on waste from the coconut rhinoceros beetle, Oryctes rhinoceros (Coleoptera: Scarabaeidae), fed cocopeat. Beetle diet and frass NPK levels, C:N ratio, and particle size were measured. Microbiota was identified with metabarcoding, and functional profile analysis done to identify pathways associated with wood digestion or plant growth. Cultivation tests were done with Arabidopsis thaliana (Brassicales: Brassicaceae) and frass incorporation into potting soil at 0, 20, or 40%, followed by elemental concentration measurement of the soil, frass, and plant matter. Results Digestion of plant polysaccharides in the gut, primarily by microbial depolymerizers, produces frass of uniform particle size and NPK 1.8–0.13–1.2 that can be used directly as a mature fertilizer without pre-composting, or even as a growth substrate. Plants with higher proportions of frass in the soil grew significantly faster and larger compared to a nutrient-rich potting soil. Frass is high in useful elements and has beneficial chitinolytic microbes. Conclusions Beetle frass can thus be used directly as a soil amendment without composting or pretreatment, with positive effects on plant growth even compared to rich soils. Valorizing frass in this way generates income for beetle farmers and recycles nutrients to soil as part of circular agriculture.